An estimate of cross-section of photo-proton reactions on ⁴⁷⁻⁵⁰Ti isotopes - Dikiy, N.P.; Zakharchenko, A.A.; Lyashko, Yu.V.; Uvarov, V.L.; Shevchenko, V.A.; Tenishev, A.Eh. (Вопросы атомной науки и техники, 2022)
Development of technology of isotope production at an electron accelerator, in particular ⁴⁷Sc by the ⁴⁸Ti(γ,p)⁴⁷Sc reaction, requires accurate data on cross-sections of this and other photo-proton reactions on the titanium isotopes, as the available data are characterized by considerable scatter. A simple technique for estimating maximum and width of the excitation function of a reaction with dominating giant dipole resonance was proposed and validated earlier. The method is based on measurement of normalized reaction yield in a thin target, overlapping completely a flux of X-rays, and processing of data obtained with the use of a developed analytical model. The joint activation of foils from natural nickel, molybdenum and titanium by bremsstrahlung radiation with end-point photon energy in the range 40…95 MeV was carried out. The characteristics of the reactions ⁴⁸Тi(γ,p)⁴⁷Sc, ⁴⁹Ti(γ,p)⁴⁸Sc, ⁵⁰Ti(γ,np)⁴⁸Sc, ⁴⁷Ti(γ,p)⁴⁶Sc, and ⁴⁸Ti(γ,np)⁴⁶Sc are studied by new technique. For verifying results, the wellexamined ⁵⁸Ni(γ,n)⁵⁷Ni and ¹⁰⁰Mo(γ,n) ⁹⁹Mo reactions, taking place in the nickel and molybdenum foils, are used. Розвиток технології виробництва ізотопів на прискорювачах електронів, зокрема ⁴⁷Sc за реакцією ⁴⁸Ti(γ,p)⁴⁷Sc, потребує більш точних даних про перерізи цієї та інших фотопротонних реакцій на ізотопах титану, оскільки наявні дані характеризуються суттєвим розкидом. Раніш був запропонований та валідований простий метод оцінки максимуму і ширини функції збудження для реакції з домінуванням гігантського дипольного резонансу. Метод заснований на вимірюванні нормованого виходу реакції в тонкій мішені, яка повністю перекриває потік гальмівних фотонів, і обробці одержаних даних з використанням розробленої аналітичної моделі. Було проведено сумісну активацію фольг з природного нікелю, молібдену та титану гальмівним випромінюванням з граничною енергією в діапазоні 40…95 МеВ. З використанням нового методу досліджено параметри реакцій: ⁴⁸Тi(γ,p)⁴⁷Sc, ⁴⁹Ti(γ,p)⁴⁸Sc, ⁵⁰Ti(γ,np)⁴⁸Sc, ⁴⁷Ti(γ,p)⁴⁶Sc, and ⁴⁸Ti(γ,np)⁴⁶Sc. Для верифікації одержаних результатів використані добре вивчені реакції ⁵⁸Ni(γ,n)⁵⁷Ni and ¹⁰⁰Mo(γ,n) ⁹⁹Mo, що відбуваються у нікелі та молібдені. Развитие технологии производства изотопов на ускорителях электронов, в частности ⁴⁷Sc по реакции ⁴⁸Ti(γ,p)⁴⁷, требует более точных данных о сечениях этой и других фотопротонных реакций на изотопах титана, поскольку имеющиеся данные характеризуются существенным разбросом. Ранее был предложен и валидирован простой метод оценки максимума и ширины функции возбуждения для реакции с доминированием гигантского дипольного резонанса. Метод основан на измерении нормированного выхода реакции в тонкой мишени, полностью перекрывающей поток тормозных фотонов, и обработке полученных данных с использованием разработанной аналитической модели. Была проведена совместная активация фольг из природных никеля, молибдена и титана тормозным излучением с граничной энергией в диапазоне 40…95 МэВ. С использованием нового метода были исследованы параметры реакций: ⁴⁸Тi(γ,p)⁴⁷Sc, ⁴⁹Ti(γ,p)⁴⁸Sc, ⁵⁰Ti(γ,np)⁴⁸Sc, ⁴⁷Ti(γ,p)⁴⁶Sc, and ⁴⁸Ti(γ,np)⁴⁶Sc. Для верификации полученных результатов использованы хорошо изученные реакции ⁵⁸Ni(γ,n)⁵⁷Ni and ¹⁰⁰Mo(γ,n) ⁹⁹Mo, которые происходят в никеле и молибдене.